(untitled) (Eurasian Medical Research Periodical, 2023)
Pregnancy complicated by gestational diabetes mellitus (GDM) is associated with a higher risk of serious obstetric and perinatal complications. Gestational diabetes mellitus is a risk factor for the development of obesity, type 2 diabetes mellitus and cardiovascular disease in the mother and offspring in the future. Results of the study Hyperglycemia and Adverse Pregnancy Outcome (HAPO) showed that the previously used criteria for diagnosing GDM require revision.